VD_FINDINFO Jug / 2016 / 155 vom 13. November 2015 - VD Tribunal cantonal (2015)
VIOLENCE CONTRE LES AUTORITÉS, CONSTATATION DES FAITS, APPRÉCIATION DES PREUVES | 285 ch. 1 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)